Expor o corpo para revelar a carne: das sensações ao pensamento em Irreversível, de Gaspar Noé - Righetti, Mario Sergio (Universidade Federal de São Carlos, 2017)
The proposal of this research is to analyze the film Irreversible (2002), by the French-Argentine filmmaker Gaspar Noé, in an effort to reflect and relativize on the thematic, aesthetic and ideological aspects present in the work, more specifically discussing the way in which the filmmaker makes use of a radical cinematography proposal that would establish a tension in the sensory and affective sharing between the body of the screen, the camera body and the viewer's body. The filmmaker is based on an aesthetic of the corporeal that presses for the existential question and at the same time for the obsession with an explicit and abject visuality that exposes the body to reveal the flesh. The cinematic body of Noé uses haptic image and sound traversing a sometimes batailleano path, through transgression, sensoriality and experimentation, which began in his earlier films Carne (1991) and I Stand Alone (1998). As we seek to point out in this work, these films are marked by the exhibition of immanent corporeity and carnal affection – through which the filmmaker's ‘obsessions’ were mapped here, as a way of finding the core of the ethical-aesthetic issues he induced and reflected in search of the subjectivity and the thought of the spectator.
Expose the body to reveal the flesh: from the sensations to the thought in Gaspar Noé's Irreversible
Keywords: Irreversível; Gaspar Noé; Corporeidade imanente; Afeto carnal; Abjeto; Pensamento; LINGUISTICA, LETRAS E ARTES::ARTES::ARTES DO VIDEO; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA; CIENCIAS HUMANAS; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO::COMUNICACAO VISUAL; LINGUISTICA, LETRAS E ARTES::ARTES::FUNDAMENTOS E CRITICA DAS ARTES::TEORIA DA ARTE